Industrial Heating Furnace Temperature Control System - Jambhale, Mahesh; Prof. S.S.Patil; Prof. A.S.Mali (International Journal of Engineering and Management Research, 2024)
PT 100 temperature sensors are the most common type of platinum resistance thermometer. Often resistance thermometers are generally called Pt100 sensors, even though in reality they may not be the RTD Pt100 type. The temperature of any equipment for every industrial application is controlled by the microcontroller-based temperature control system. At its heart lies the Arm 9 microprocessor, which performs the circuit’s entire operations Industrial Heating furnace (IHF) .Temperature, is sensed using the PT 100 temperature sensor, which acts linearly with temperature increase. This temperature is compared to the user-saved value, and if it exceeds the preset temperature, the heater turns off; if it falls below the preset value, the heater turns on. An LCD panel displays both the asking and real-time temperatures with human machine interface (HMI). The microcontroller automatically switches on/off a heater or a fan based on the conclusion of the comparison. This proposed paper is separated into two modules, one for temperature monitoring and the other for data collection and also link to personal computer.